Effect of Oropharyngeal Administration of Mother's Milk Prior to Gavage Feeding on Gastrin, Motilin, Secretin, and Cholecystokinin Hormones in Preterm Infants: A Pilot Crossover Study. Issue 4 (25th June 2020) - Mohammed, Abdel‐Rahman; Eid, Abdel‐Rahman; Elzehery, Rasha; Al‐Harrass, Mohammad; Shouman, Basma; Nasef, Nehad
Abstract: Background: Oropharyngeal administration of milk prior to gavage feeding has been shown to improve feeding tolerance in preterm infants. Objectives: The aim is to study the effect of oropharyngeal administration of mother's milk (OPAMM), prior to gavage feeding, on the levels of gastrin, motilin, secretin, and cholecystokinin hormones. Methods: Preterm infants (<32 weeks' gestation) were randomized at a corrected gestational age of 33–34 weeks, in a crossover design, to receive 1 of 2 protocols: 24 hours of OPAMM practice (applying 0.2 mL of mother's milk prior to each gavage feeding) followed by 24 hours of regular gavage‐feeding practice in the first protocol or vice versa in the second protocol. The levels of gastrin, motilin, secretin, and cholecystokinin hormones were measured at the end of 24 hours of both practices. Results: The data of 40 preterm infants (20 in each protocol) were analyzed. OPAMM was associated with a significant increase in the levels of motilin (median, 233; interquartile range [IQR], 196–296 vs median, 196; IQR, 128–233; P < .01), secretin (median, 401; IQR, 353–458 vs median, 370; IQR, 331–407; P = .04), and cholecystokinin (median, 21.4; IQR, 16–27.1 vs median, 14.9; IQR, 11–20.5; P <.01) but not gastrin (median, 202; IQR, 125–238 vs median, 175; IQR, 128–227; P = .7), compared with regular gavage‐feeding practice. Conclusion: Oro‐pharyngeal stimulation by OPAMM, prior to gavage feeding, significantly increased motilin hormone and possibly increased secretin and cholecystokinin hormones.